2021
DOI: 10.46827/ejoe.v6i1.3665
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and Mental Resilience of Children, Parents, in Greek Kindergarten Schools During the New Era of Pandemic Covid-19. Teachers' Views

Abstract: The pandemic of Covid-19 has invaded in our lives, with multiple and multidimensional challenges. During the close of school units in Greece at March, teachers were initially used types of distance education, while with the opening of the schools during June they had to face issues, such as the separation of classes, the observance of distances, the use of medical mask, experiencing a new, unprecedented situation. In this paper, reference will be made to key issues of adaptation and mental resilience of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 4 publications
(4 reference statements)
2
19
0
3
Order By: Relevance
“…The few available studies on the distance education practices of Greek teachers during the COVID‐19 pandemic suggest that despite the sudden shift to a pure distance learning mode they managed to respond successfully to the challenge (Nikiforos et al, 2020). Initially, Greek preschool teachers adopted mainly asynchronous forms of distance education to maintain the communication with their students and support their students (Foti, 2020). At a later stage, they adopted synchronous forms of distance teaching with technical problems such as limited resources, limited support for children at home and limited experience of using information communication technology emerging as important obstacles to overcome (Nikolopoulou, 2022).…”
Section: Teachers' Resilience During Covid‐19mentioning
confidence: 99%
See 1 more Smart Citation
“…The few available studies on the distance education practices of Greek teachers during the COVID‐19 pandemic suggest that despite the sudden shift to a pure distance learning mode they managed to respond successfully to the challenge (Nikiforos et al, 2020). Initially, Greek preschool teachers adopted mainly asynchronous forms of distance education to maintain the communication with their students and support their students (Foti, 2020). At a later stage, they adopted synchronous forms of distance teaching with technical problems such as limited resources, limited support for children at home and limited experience of using information communication technology emerging as important obstacles to overcome (Nikolopoulou, 2022).…”
Section: Teachers' Resilience During Covid‐19mentioning
confidence: 99%
“…| 1461 education to maintain the communication with their students and support their students (Foti, 2020). At a later stage, they adopted synchronous forms of distance teaching with technical problems such as limited resources, limited support for children at home and limited experience of using information communication technology emerging as important obstacles to overcome (Nikolopoulou, 2022).…”
Section: The Case Of Greecementioning
confidence: 99%
“…3) which is an attractive programmable floor robot for young children that is an easy way of introducing programming into the classroom and, its flexible nature also means that it can be used with children up to 8 years old and can help develop other areas of the curriculum in addition to ICT. Beebot is programmed with on-board buttons and can be programmed to move precisely in space by moving forward, backward, turning left and right while its simple and child-friendly layout makes it a perfect starting point for teaching control, direction (orientation) and programming language to young children (Foti, 2018, 2020, Foti, Rellia, 2020. Many schools have found that the Bee-Bot can help children develop computational thinking skills and/or reinforce concepts that other resources or methods do not use.…”
Section: Robots and Learning Environmentsmentioning
confidence: 99%
“…The first STREAM Learning Scenario that follows relates to the Natural Sciences and specifically the Time of Year Title: "Seasons of the year" (Foti, 2020). Description Subject: Natural sciences Subject/Study module: Seasons Goal: To learn the seasons of the year Summary: Students navigate with the Bee-Bot at the epoch-in-place, either on a cardboard (in dimensions 6 by 15cm ) or on a transparent grid placed in images by those epochs (image 1).…”
Section: Linking Theory To Practice St(r)eam Learning Scenariosmentioning
confidence: 99%
“…3) Emocionalna regulacija kao bitan preduslov za pružanje podrške najmlađima u stresnim situacijama (Kruger i Reddemann, 2013;Profaca i Arambašić, 2009) uočava se u izjavama vaspitača. Istražujući adaptaciju djece na vrtić i školu u doba COVID-19 Foti (2021) uviđa potrebu adaptacije ne samo djece, nego i odraslih bitnih za dijete na novonastalu situaciju. Iz izjava slovenačkih i bosanskohercegovačkih vaspitača primjećuje se dobra pripremljenost i prilagodljivost za novonastalu situaciju u vrijeme pandemije COVID 19, što je blisko rezultatima istraživanja u Srbiji (Stoiljković, 2020).…”
Section: … Bili Su Jako Veseli šTo Se Opet Vide I Igraju Zajedno Posebno Su Starija Djeca Bila žEljna Zajedniče Igre Ali I Manja (Segmentunclassified